Critical success factors of sustainable project management in construction: A fuzzy DEMATEL-ANP approach. (1st September 2018) - Kiani Mavi, Reza; Standing, Craig
Abstract: There is an extensive number of factors that influence the success and failure of projects, however, literature lacks an inclusive categorization of them especially in construction. This paper aims to identify critical success factors (CSFs) of project management and categorize them into five criteria groups: (1) project, (2) project management, (3) organization, (4) external environment and (5) sustainability. To determine the interdependence and weight of the CSFs, data was gathered from 26 Australian project managers from the construction industry. The contribution of the paper is in identifying cause and effect criteria of CSFs and in identifying their weights. Using the fuzzy decision making and evaluation laboratory (fuzzy DEMATEL) method it is shown that the organization, external environment and sustainability are "cause" criteria, while project and project management are identified as "effects". The fuzzy analytic network process (fuzzy ANP) is used to weigh the sub-criteria by considering the interdependence of the main criteria. The findings revealed that the highest weights are assigned to top management and sponsor support (s ), stakeholder expectations ( w 45 = 0.050 ) and end users imposed restrictions ( w 41 = 0.039 ), respectively. Project managers can significantly improve project success by focusing on more important critical success factors rather than paying equal attention to all of them. Graphical abstract: Image 1 Highlights: Comprehensively reviews project management critical success factors (CSFs). Distinguishes sustainability CSFs in project management. The organization, external environment and sustainability CSFs are "cause" criteria. Project and project management CSFs are "effect" criteria. Top management and sponsor support is the most important factor in construction.